The effect of mental imagery training in developing accuracy and speed of basic badminton skills among beginner players / Habeeb Y. Kasim - Y. Kasim, Habeeb (2013)
Background of study: the study investigates the effect of the mental imagery training in developing a specific movements in badminton, to be more specific, this study is looking at increasing the accuracy and speed of response of basic badminton skills (serve, forehand, backhand) through the modifications of motor skills and neuromuscular process through mental imagery training.Purpose: The main purpose of the study is to investigate the effect of mental imagery training to develop the accuracy and speed of response of basic badminton skills (long and short serve, forehand and backhand). Method: The researcher applied an experimental design on this study. The subject were (N=40) beginners badminton players selected through stratified random sampling from badminton academy at Petaling Jaya. The subjects were divided on four equal groups with each groups consisted of n= 10 Players. The control groups were restrained from conducting any physical or mental imagery trainings. The other groups used combination of physical, mental imagery, visual and verbal training methods. Result: The results of paired sample t test had showed significant differences for all experimental groups between pre and post tests. The results also shown that there is significant different (F=3.42, p<0.031) in physical training in combination with mental imagery and verbal stimulus group than the other physical and mental imagery training groups. Findings: The findings suggested that combination between physical training and mental imagery training with verbal stimulus increased the accuracy and speed of basic badminton skills. This Finding is similar with past studies, however, further study need be done to determine the application of mental imagery training in other type of sports.